On the identity of Cancer urania Herbst, 1801 (Crustacea: Decapoda: Brachyura: Leucosiidae) - Ng, Peter K.l.; Türkay, Michael; Galil, Bella S. (Zootaxa, 2014)
Cancer urania Herbst, 1801, is the type species of the leucosiid genus Coleusia Galil, 2006. Its identity has been a subject of confusion due to various taxonomical and nomenclatural issues. We redescribe the species, discuss its complex history and taxonomy, and a female syntype is designated as the lectotype of the species to clarify any lingering ambiguities concerning the type material of Cancer urania Herbst, 1801.